Pengaruh Model Pembelajaran Kooperatif dan Kecerdasan Emosional Terhadap Tanggung Jawab Siswa Dalam Mata Pelajaran Pendidikan Jasmani Olahraga Yayasan Pendidikan SMP Santo Xaverius 1 Kabanjahe - Roy Bastian Tarigan; Abdul Munir; M. Rajab Lubis (Universitas Medan Area, 2020)
The objectives of this study are: (1) To find out the significant effect differences between the use of Student Teams Achievement Divisions (STAD) learning methods and Jigsaw learning methods on student responsibility, (2) To determine the significant difference in influence between students who have emotional intelligence towards student responsibility, (3) To determine the interaction of influence between learning models and emotional intelligence on student responsibility. The subject of this study was the eighth grade students of Santo Xaverius 1 Junior High School, namely class VIII-1 who used the STAD learning method and class VIII-3 using the Jigsaw method. The results of the study were: (1) the average responsibility of students taught by the Jigsaw learning method = 87.96 higher than the learning outcomes of students taught by the STAD learning method = 66.3 with Fcount = 1.127 Ftable = 4.006, (2) the average responsibility of students with high emotional intelligence = 86.68 higher than the responsibility of students with low emotional intelligence = 60.76 with Fcount = 7.749 Ftable = 4.009, (3) There is no interaction between learning models and emotional intelligence on student responsibility with Fcount = 2.239 Ftable = 2.683